Peripheral Voltage-Gated Cation Channels in Neuropathic Pain and Their Potential as Therapeutic Targets - Alles, Sascha R. A.; Smith, Peter A. (Frontiers in Pain Research, 2021)
The persistence of increased excitability and spontaneous activity in injured peripheral neurons is imperative for the development and persistence of many forms of neuropathic pain. This aberrant activity involves increased activity and/or expression of voltage-gated Na+ and Ca2+ channels and hyperpolarization activated cyclic nucleotide gated (HCN) channels as well as decreased function of K+ channels. Because they display limited central side effects, peripherally restricted Na+ and Ca2+ channel blockers and K+ channel activators offer potential therapeutic approaches to pain management. This review outlines the current status and future therapeutic promise of peripherally acting channel modulators. Selective blockers of Nav1.3, Nav1.7, Nav1.8, Cav3.2, and HCN2 and activators of Kv7.2 abrogate signs of neuropathic pain in animal models. Unfortunately, their performance in the clinic has been disappointing; some substances fail to meet therapeutic end points whereas others produce dose-limiting side effects. Despite this, peripheral voltage-gated cation channels retain their promise as therapeutic targets. The way forward may include (i) further structural refinement of K+ channel activators such as retigabine and ASP0819 to improve selectivity and limit toxicity; use or modification of Na+ channel blockers such as vixotrigine, PF-05089771, A803467, PF-01247324, VX-150 or arachnid toxins such as Tap1a; the use of Ca2+ channel blockers such as TTA-P2, TTA-A2, Z 944, ACT709478, and CNCB-2; (ii) improving methods for assessing “pain” as opposed to nociception in rodent models; (iii) recognizing sex differences in pain etiology; (iv) tailoring of therapeutic approaches to meet the symptoms and etiology of pain in individual patients via quantitative sensory testing and other personalized medicine approaches; (v) targeting genetic and biochemical mechanisms controlling channel expression using anti-NGF antibodies such as tanezumab or re-purposed drugs such as vorinostat, a histone methyltransferase inhibitor used in the management of T-cell lymphoma, or cercosporamide a MNK 1/2 inhibitor used in treatment of rheumatoid arthritis; (vi) combination therapy using drugs that are selective for different channel types or regulatory processes; (vii) directing preclinical validation work toward the use of human or human-derived tissue samples; and (viii) application of molecular biological approaches such as clustered regularly interspaced short palindromic repeats (CRISPR) technology.